Sheet Metal 2015 - Merklein, Marion; Duflou, Joost R.; Leacock, Alan G.; Micari, Fabrizio; Hagenah, Hinnerk (FAU University Press, 2015)
Collection of selected, peer reviewed papers from the 16th International Conference on Sheet Metal (SheMet 2015), March 16-18, Erlangen-Nürnberg, Germany. The 70 papers are grouped as follows: Chapter 1: Keynote; Chapter 2: Forming; Chapter 3: Bending; Chapter 4: Incremental Forming; Chapter 5: Hot Stamping; Chapter 6: Sheet-Bulk Metal Forming; Chapter 7: Materials Testing; Chapter 8: Modelling; Chapter 9: Cutting and Joining; Chapter 10: Planning; Chapter 11: MatProFutu
Keywords: Forming of Sheet Metal; Hot Stamping; Incremental Forming; Materials Testing; Modelling; Sheet Metal; Sheet-Bulk Metal Forming